If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3b + a) = 0 Reorder the terms: 4(a + 3b) = 0 (a * 4 + 3b * 4) = 0 (4a + 12b) = 0 Solving 4a + 12b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12b' to each side of the equation. 4a + 12b + -12b = 0 + -12b Combine like terms: 12b + -12b = 0 4a + 0 = 0 + -12b 4a = 0 + -12b Remove the zero: 4a = -12b Divide each side by '4'. a = -3b Simplifying a = -3b
| 2x+45+3x-20=180 | | x^2+16x+243=180 | | -2x=-35.24 | | 2x+4(y-3)=10y-8x | | 425=x+365 | | 13-x=36 | | x^3+21x+6=0 | | (ab+3a+7)-(-5ab-2)= | | x-y+2=1 | | 2y=10+4x | | -2y=3x-10 | | 5(3x-6)=4(10x+15) | | x^2+x-510=0 | | 3*x(x+3)=180*180 | | x-t+21=x-21-t | | 21-x=71-x | | x-21=x-71 | | log(X)=2.79 | | 2y-1y=0 | | XY(X^2+Y^2)=47.3 | | 300=100e^5x | | y=.50(6x-8) | | (8x+5)=13 | | 3ln(2)-3ln(3)= | | X*Y*(X^2+Y^2)=3.47 | | 14b-2=419b+33 | | 20=.08x | | y+3=-9-y | | 13-2x=4x-5 | | 14-x=2x+5 | | 9x+5y+6z-4x+2z-6y= | | 3[7-2(7x-4)]=-42x+45 |